PENGARUH PENGETAHUAN INVESTASI DAN MOTIVASI INVESTASI TERHADAP MINAT INVESTASI MAHASISWA POLITEKNIK KEUANGAN NEGARA STAN DI PASAR MODAL - Rizky Achmad Firdaus; Nur Ifrochah (Jurnal Acitya Ardana, 2022)
This research aims to determine the effect of investment knowledge and investment motivation on student investment interest in the capital market. The research design in this study was a mixed method, which was a combination of qualitative research and quantitative research. The data used in this study was primary data. The data collection technique was done by using a questionnaire and conducting interviews. The research was conducted in Polytechnic of State Finance STAN with the research population were students of the Diploma IV Regular Accounting study program class of 2017 and regular students of all departments class of 2018 and 2019. The number of samples in this research were 135 students with the sampling technique that was convenience sampling. The research instrument was tested by validity and reliability tests, while the data analysis technique was done by classic assumption test, simple regression analysis, and multiple regression analysis. The results shows that there is an effect of investment knowledge on student investment interest in the capital market, there was an effect of investment motivation on student investment interest in the capital market, and there was a simultaneous effect between investment knowledge and investment motivation on student investment interest in the capital market.